A multi-dimensional sustainability assessment of marine protected area management in Jemur Island on the Malacca Strait, Indonesia - TRISLA WARNINGSIH; TOMI RAMADONA; ZULKARNAIN ZULKARNAIN; NURAINI NURAINI; RINETA KHAIRUNISSA; DEVIASARI DEVIASARI; ANDINI MUTHMAINNAH; ASWANDI ASWANDI (Society for Indonesian Biodiversity, 2026)
Abstract. Warningsih T, Ramadona T, Zulkarnain, Nuraini, Khairunissa R, Deviasari, Muthmainnah A, Aswandi A. 2026. A multi-dimensional sustainability assessment of marine protected area management in Jemur Island on the Malacca Strait, Indonesia. Biodiversitas 27 (1): d270140. https://doi.org/10.13057/biodiv/d270140. Jemur Island in the Aruah Islands archipelago in the Malacca Strait, Riau Province, Indonesia, is a marine protected area (MPAs) with significant ecological value as a nesting habitat for green turtles and various economically valuable fish species. However, pressure from human activities and institutional limitations pose challenges to its sustainable management. This study aims to assess the sustainability of marine protected area management on Jemur Island using the Rapfish (Rapid Appraisal for Fisheries) method through a Multi-dimensional Scaling (MDS) approach across four dimensions: ecological, economic, social, and institutional. Data were obtained from in-depth interviews with stakeholders and field observations in mid-2024. The ecological dimension scored 61.44, indicating moderate sustainability, driven primarily by coral reef conditions and turtle nesting habitat quality, with fish abundance identified as the key leverage attribute. The economic dimension scored 64.08, also moderately sustainable, supported by fisheries-based livelihoods and emerging ecotourism, while resource dependency emerged as the critical leverage variable. In contrast, the social dimension scored 41.94, reflecting weak sustainability, with community awareness and participation identified as its main sensitivities. The institutional dimensions were categorized as less sustainable, scored 42.63, and similarly weak, largely influenced by coordination effectiveness and the adequacy of local management capacity. Pareto and leverage analysis further highlight that improvements in fish abundance, livelihood diversification, community engagement, and institutional strengthening offer the greatest potential to enhance overall sustainability. These findings emphasize the need for targeted, evidence-based management and interventions that prioritize ecological monitoring, community involvement, and institutional capacity building. The study provides a structured baseline for evaluating MPA performance in small-island settings and supports future efforts to design more adaptive and participatory conservation strategies.